반응표면분석을 이용한 PoN 블록체인 시스템 합의품질 개선 - 최진영; 김영창; 오진태; 김기영 (품질경영학회지, 2021)
Purpose: The purpose of this study was to suggest an improved version of Proof-of-Nonce (PoN) algorithm, which is a distributed consensus algorithm used for block chain system. Methods: First, we used response surface method for design of experiment that is to generate experimental points considering non-linear relationship among variables. Then, we employed overlapped contour plots for visualizing the impact of control variables to performance target. Results: First, we modified the consensus procedure of the existing PoN algorithm by diminishing the content of the exchanged message. Then, we verified the performance improvement of the new PoN algorithm by performing a numerical experiment and paired t-test. Finally, we established new regression models for consensus time and Transactions per second (TPS) and proposed a method for optimizing control variables for obtaining performance target. Conclusion: We could improve the performance of the previous version of PoN algorithm by modifying the content of the exchanged message during 4-steps of consensus procedure, which might be a stepping stone for designing an efficient and effective consensus algorithm for blockchain system with dynamic operation environment.
Keywords: Blockchain; Proof-of-Nonce; Distributed Consensus Algorithm; Consensus Qualtiry; Response Surface Method